La Declaratoria de Abandono Procesal en Materia no Penal sin permitir Justificación alguna del Accionante Vulnera el Derecho Constitucional a la Defensa - Armijos Andrade, Marjorie Cristina (2016)
Legal process begins with the filing of the complaint and followed this must comply with all formalities and established measures in advance in the law, up to the culmination of this is with the sentence ending the process so normal and ordinary fulfilling the order with which it began, but this can be seen truncated with termination means indirectly such as the raid, abandonment, desertion, and neglect to transaction. Speaking of abandonment procedural, legal figure that is the main object of study of this research, we refer to the act by which neglects certain things or people including rights, which is why abandonment is taken as a legal and It is given explicitly in judicial proceedings in which it has stopped processing them for a period of time and is passively at the time the law provides, thus giving terminate a procedural step because once declared himself it has not been reached to settle the dispute being raised to settle the pending litigation. In our legal system this figure is stipulated in the Organito Code General Process (COGEP), from Article 245 to Article 249, being a new code there are several loopholes and rights violated fundamental principles and figure abandonment procedure is no exception, which is why it is necessary to make a thorough study of this procedural figure in our legal system and the rights and principles that are violated with such declaration by comparative law. In this research entitled "Statement of Procedural Abandonment in non criminal matters without allowing any justification of the plaintiff violates the constitutional right to defense", it is making conscientious legislator who is wrong having given the power of res judicata to the declaration which leads to the abandonment procedure since the same ends the process but not the conflict is solved presented preventing people from accessing a second time to the court to enforce their rights violated; then, without allowing it to justify its abandonment is violated their right to defense and the principle of effective judicial protection that the State is the main velador the same as the access to justice. The notable difference that brings this new code concerning this figure is that once already issued the order with the declaration of abandonment and notified the parties that may be challenged for one reason, which is if an error was committed computing in the term to be dictated by the court; the same does not result that the plaintiff can challenge that is, if the judge when issuing an order for abandonment was computed 79 days or less from the last working diligently or notification of the last providence, can challenge the car dictated abandonment, thus constituting a limitation to the exercise of the right to defense of persons unable to challenge whether the car if not an error of calculation in the days. Should be taken into consideration that the plaintiff if have the possibility to justify the abandonment of a process, for duly justified and verified, because the rights of individuals can not be seen violated by a simple interlocutory order that declared abandonment, taking that this drop reflects the principle of judicial economy, but to do if for procedural economy are to abandon processes that can challenge their abandonment; as in the case of the death of the plaintiff, it is something that the sponsor lawyer not expected before, and this person die your heirs will not be able to exercise their right violated, being dictated abandonment. It will be the total disagreement of citizens by delivering the power of res judicata an interlocutory order since our country is the one who delivers the power of res judicata abandoned the car; as well as the interlocutory orders made by administrators of justice. It is knowledge for many who previously were allowed to re-submit a new application for the same reason after declared, without a limit of the time, making it a waste of funds invested in the process, the courts were filled with unnecessary processes the initiated and the parties had no interest to continue them, whereas now gone to the extreme with this declaration by truncating the right people to be able to file a new lawsuit once if justified correctly abandonment either cases acts of God or force majeure duly verified. It should be considered important aspects, so this research are directed to the plaintiff be allowed platear demand again whenever justify why the abandonment of the process took place, and you can not let the affected right not it is claimed, thus violating not only the right to defense if not many more rights and basic principles, and the State must ensure faithful compliance with them.